Mortgage Securities in Emerging Markets - Chiquier, Loïc (World Bank, Washington, D.C., 2013)
Despite its recognized economic and social importance, housing finance often remains underdeveloped in emerging economies. Residential lending remains small, poorly accessible, and depository-based. Lenders remain vulnerable to significant credit, liquidity, and interest rate risks. As a result, housing finance is relatively expensive and often rationed. The importance of developing robust systems of housing finance is paramount as emerging economy governments struggle to cope with population growth, rapid urbanization, and rising expectations from a growing middle class. The capital markets in many economies can provide an attractive and potentially large source of long-term funding for housing, and solutions to better allocate part of the risks. The advent of institutional investors is creating large and rapidly growing pools of funds that may facilitate the development of mortgage-related securities. Despite such a strong appeal, there are significant barriers to the development of mortgage securities in emerging markets. Their success is dependent on many factors, starting with a strong legal and regulatory framework and liberalized financial sector, and including a developed primary mortgage market. The experience in developing mortgage securities in emerging markets has been mixed. The authors review the experience of introducing mortgage securities in emerging markets and explore the policy issues related to this theme.